On the use of Video Based analysis and coding for solving problems in mechanics - Sarkar, Shivalika; Vajpayee, Amritanshu (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Creating constructivist inquiry based active classrooms the teacher has to resort to new methods of teaching. To make mechanics concepts more meaningful and visible we propose the use of an open source software Tracker, which can be easily downloaded.  Teaching of fundamental concepts of mechanics can be easily done by visualizing and analyzing the motion of the objects in the Tracker software environment.  In this article we deal with some mechanics problems (free fall, determination of acceleration of mass in string using Atwood machine, coefficient of restitution and simple harmonic motion) and how they can be visualized and solved using the tracker software. This software can be very useful right from high school students to college students for analyzing different types of motions. This method is also known as video based analysis (VBA) method. This method can widely be used across different problems of mechanics and can be helpful in effective teaching learning process. Coding is a necessary skill that all students need regardless of their field. It helps them visualize the problem and hence understand it more deeply in some cases. In this paper we also present the results of using coding and video analysis for selected mechanics problems on a group of students. These approaches help the students in visualizing the mechanics problems and also developing the mathematical modeling skills.